(untitled) (Management and Connections Journal, 2023)
Given the little production on the subject of black women workers in the area of Organizational Studies, we proposed to analyze the biographies of researchers on the subject and understand the imbrications of scientific work with their personal trajectories. After conducting interviews with authors of texts that address the investigated theme, we resorted to Ricoeur (1995) weaving of intrigues to analyze the data and conclude that the biographies are indeed imbricated with the scientific doings of the researchers. However, we highlight the biographies of black women who seek to transgress the racist optics of the academic environment by publicizing the intersection of race and gender and friction the normative standard, creating space for an education that recognizes and gives credibility to the human experience (and knowledge) in its diversity.